2012
DOI: 10.1002/ardp.201100225
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Antihyperlipidemic Activity of a New Series of N‐(Benzoylphenyl) and N‐(Acetylphenyl)‐1‐benzofuran‐2‐carboxamides in Rats

Abstract: A new series of N-(benzoylphenyl) and N-(acetylphenyl)-1-benzofuran-2-carboxamides (3a-3d and 4a'-4c') were synthesized. Compounds (3a, 3b, and 4a'-4c') were tested in vivo using Triton-WR-1339-induced hyperlipidemic rats as an experimental model for their hypolipidemic activity. The tested animals were divided into eight groups: control, hyperlipidemic, 3a, 3b, 4a', 4b', 4c', and bezafibrate. At a dose of 15 mg/kg, the elevated plasma triglyceride (TG) levels were significantly reduced in compounds 3b (p <0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…5,6) Our previous published data has shown that many of the synthesized carboxamide derivatives exhibited noticeable antihyperlipidemic activity. [7][8][9][10][11][12] It was postulated that the hypolipidemic activity of the carboxamides is correlated with the presence of three essential parts: a large lipophilic moiety, an aromatic carboxamide linker along with a heterocyclic ring. 11) Although the significant biological activity, almost all earlier developed carboxamides suffered from water solubility deficiencies hindering biological testing and affecting negatively pharmacological activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5,6) Our previous published data has shown that many of the synthesized carboxamide derivatives exhibited noticeable antihyperlipidemic activity. [7][8][9][10][11][12] It was postulated that the hypolipidemic activity of the carboxamides is correlated with the presence of three essential parts: a large lipophilic moiety, an aromatic carboxamide linker along with a heterocyclic ring. 11) Although the significant biological activity, almost all earlier developed carboxamides suffered from water solubility deficiencies hindering biological testing and affecting negatively pharmacological activity.…”
mentioning
confidence: 99%
“…These observed deficiencies inspired the design and synthesis of novel compounds with improved water solubility profile. In a first attempt there was the design of benzimidazole-2-carboxamide derivatives that showed improved water solubility over all previous derivatives providing both feasible pharmacological testing due to easier solubilization and comparable pharmacological profile, 13) this has led to the introduction of the imidazole-5-carboxamides possessing an imidazole ring which is characterized by a low pK a value (pK a =6.9) in comparison with the pK a values of the previous aromatic heterocyclic rings (Benzimidazole pK a =16.4, indole pK a =21, furan pK a =35.6, and thiophene pK a =33) present on the previously published carboxamide derivatives [6][7][8][9][10][12][13][14] (Fig. 1).…”
mentioning
confidence: 99%
“…In the last decade, many studies have shown that furan derivatives have promising potentials as lipid-lowering agents [15][16][17]. Therefore, the present study focuses on the synthesis and pharmacological evaluation of a novel series of N-(benzoylphenyl)-2-furamides as models for their lipid-lowering activity ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Triton WR‐1339‐induced hyperlipidemia in rats is a widely accepted animal model , successfully used for screening lipid‐lowering activities of natural products and chemical entities, since it is simple to handle and requires shorter time to induce hyperlipidemia . The administration of single intraperitoneal dose of Triton WR‐1339 to adult rats has been reported to increase TC, LDL‐C, and TGs to reach a maximum value in about 20 h and return to normal thereafter .…”
Section: Discussionmentioning
confidence: 99%
“…injection of 300 mg/kg Triton WR‐1339 dissolved in water. Dose was selected based on literature recommendations where Triton WR‐1339 has been reported to be used in doses ranging from 200 mg/kg to 400 mg/kg intraperitoneally for hyperlipidemia induction . Triton WR‐1339 group was compared with a control group of six healthy rats receiving i.p.…”
Section: Methodsmentioning
confidence: 99%